Events, Social Memories, and Community in a Final Bronze Age Building's Biography at Sant'Aniceto, Calabria, Italy. (3rd October 2019) - Chesson, Meredith S.; Wolff, Nicholas P. S.; Robb, John; Yoon, David; Michelaki, Kostalena; Fiore, Ivana; Gillings, Mark; Tagliacozzo, Antonio; Taylor, Jeremy; White, Chantel E.
ABSTRACT: Archaeologists investigating Middle Bronze to Early Iron Age periods (1600–900 b.c. ) in southern Italy often explore linkages between emerging inequality and foreign trade connections, establishing a coupled trope of "change emerges from external forces" and "waiting for civilization to arrive". Based on excavations at the Recent/Final Bronze and Early Iron Ages (RFBA/IA, 1200–900 b.c. ) site of Sant'Aniceto in Calabria, we offer an alternative narrative in which hierarchy and institutionalized inequality held little sway in this community. By employing a building biography approach, we examine the variety of ways people sustain their communities through the creation and value of difference (e.g., age, knowledge, or skill) that characterize daily life, even when political hierarchy is absent. Our research at Sant'Aniceto centers on understanding the locally-grounded experiences and lives of people by approaching social difference through the lens of the materialities of everyday life.